Tradurre i modernismi: Introduzione - Binelli, Andrea; De Villa, Massimiliano; Londero, Renata; Visinoni, Alessandra (Ticontre. Teoria Testo Traduzione, 2023)
Introduzione alla sezione monografica Tradurre i modernismi.